2009
DOI: 10.1248/jhs.55.363
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Fate of Sunscreen Agents Octyl-4-methoxycinnamate and Octyl-4-dimethylaminobenzoate in Model Swimming Pools and the Mutagenic Assays of Their Chlorination Byproducts

Abstract: Reactions of sunscreen agents, octyl dimethyl-p-aminobenzoate (ODPABA) and octyl-p-methoxycinnamate (OMC), with hypochlorite in aqueous solution were investigated under the conditions that simulate swimming pool disinfection sites. Chlorination byproducts were determined by GC-MS. At a concentration of 9 µM, ODPABA reacted rapidly with free chlorine in the buffered solution at pH 7.0, OMC reacted with hypochlorite reasonably slowly under the same condition. ODPABA and OMC produced chlorine-substituted compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 26 publications
8
49
0
1
Order By: Relevance
“…However, these TPs are considered as unstable intermediates, which normally suffer further rearrangements, or are simply back converted to their precursors by reaction with the quenching reagent or any moderate reductor present in the medium. It is likely that this behavior is responsible for differences between the number and type of TPs found for certain amine compounds, such as EHPABA, without considering a reductor to remove the excess of chlorine [35] and using Na 2 S 2 O 3 as quencher [19]. In the latter study only aromatic halogenated TPs were noticed; whereas, N-demethylation by-products were also reported in the former case.…”
Section: Overview Of Typical Reaction Mechanisms During Free Chlorinementioning
confidence: 82%
See 2 more Smart Citations
“…However, these TPs are considered as unstable intermediates, which normally suffer further rearrangements, or are simply back converted to their precursors by reaction with the quenching reagent or any moderate reductor present in the medium. It is likely that this behavior is responsible for differences between the number and type of TPs found for certain amine compounds, such as EHPABA, without considering a reductor to remove the excess of chlorine [35] and using Na 2 S 2 O 3 as quencher [19]. In the latter study only aromatic halogenated TPs were noticed; whereas, N-demethylation by-products were also reported in the former case.…”
Section: Overview Of Typical Reaction Mechanisms During Free Chlorinementioning
confidence: 82%
“…As a general rule, hypochlorous acid (HClO), pK a 7.5, is more reactive than the hypochlorite anion (ClO À ); thus, transformation reactions are favored when the acidbase equilibrium is shifted to the neutral form of the acid [34]. This statement explains why non-ionizable ECs, for example, the UV filters 2-ethylhexyl-p-methoxycinnamate (EHMC) and EHPABA [35], and phenazone-type analgesics [36] display minimum t 1/2 values at pHs below 7.5. The above rule is also valid to predict the effect of chlorine on the reactivity of ECs existing as ionized species at the natural pH (5-9) of water samples, under the condition that the ionized functionality is not involved in the reaction with free chlorine.…”
Section: Factors Influencing the Kinetics Of Chlorinationmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20] Furthermore, Nakajima et al showed that the chlorination of water containing OMC increased the mutagenic activity of water. 21 In consequence to these concerns, investigations about the occurrence and behavior of UV filters in the environment have increased in the last few years. 22 Some studies investigated the fate of UV filters when exposed to chemical oxidants or light.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide further insight into the possible role of organic compounds in the formation of chlorine-substituted compounds and chlorine-induced mutagens, this laboratory has continued the study of the aqueous chlorination chemistry of organic compounds (Nakamura et al, 2008;Nakajima et al, 2009;Kawakami et al, 2009). The present report describes a detailed study of the products distribution for four hetero-tricyclic aromatic hydrocarbons (H-TCAHs), which were selected because of their widespread use in pharmaceutical and textile manufacturing industries, and as a suppressor in the polymerization of vinyl acetate, acrolein and acrylic acid.…”
Section: Introductionmentioning
confidence: 99%